The Effect of Relationship Marketing Factors toward Consumer Loyalty of PT. Astra International Tbk - Toyota Kijang Innova: Special on Commercial Car Category I in Surabaya - Achmad Daengs, GS (Fakultas Ekonomi Universitas 45 Surabaya, 2013)
In the level of competition that was increasingly competitive as in recently, then that needs to be addressed is the effort to increase the sense of loyalty of existing customers by optimizing the forms of services. One of the business strategies in face of the competitive situation that happened so the companies did not lose their customers was by creating Relationship Marketing. In Relationship Marketing to retain customers precisely was the challenge that is very heavy in comparison with looking for the new customers. It can be expected that the costs to attract the new customers has five times more expensive than to maintain a relationship with existing customers. Therefore the roles of Relationship Marketing are absolutely necessary in order to meet the need and satisfaction of customers, so that the customers remain as the loyal customers. This study entitled “The Effect of Relationship Marketing Factors toward Consumer Loyalty of PT. Astra International Tbk - Toyota Kijang Innova Special on Commercial Car Category I in Surabaya” is conducted to determine whether there are effects of benefits that offered by PT. Astra International Tbk - Toyota Kijang, Branch of Surabaya Basuki Rachmat on Consumer Loyalty. By using multiple linear regression equation analysis, the independent variables that consist of Financial Benefits, Social Benefits, and Structural Benefits simultaneously have a significant effect to the dependent variable.